IMPLEMENTASI PEMURIDAN JEMAAT KRISTEN USIA PAUD DI SEKOLAH GRACIA-BATAM - Pranada Pane; Johannes Hutabarat; Tony Suhartono; Intan Suriyanti (JURNAL BEATITUDES, 2024)
Abstract In Christianity, discipleship can be given to anyone, whether to children, teenagers, young people, even the elderly. Discipleship is an important step that must be applied to every believer. As long as the believer is able to understand and understand what discipleship is, it can be given to them. Preschool age is an age that has an estimated age limit of three to five years and this can accept discipleship, although it needs to be done in a good way that is appropriate to the level of understanding of preschool age children themselves. This really requires special attention in implementing or carrying out this discipleship for them because when they get the discipleship well, they will also accept and do what they get from the discipleship. Discipleship is a strategic step to be implemented even though you have to look at the context so that it can be implemented well and get maximum results because the goal of discipleship itself is how the people in it really get something and then they also experience life changes from the spiritual growth that occurs. in their life.